Adding the Dots and crossing the Ts: A historiographical overview of African theatre history - Ismaila, Margaret; Akakpo, Samuel Bewiadzi (Research Journal in Advanced Humanities, 2020)
The historiography of Africa has often needed an update or review because it is no news how African history was constructed; a product of colonial and anthropological records. Due to this, attention was not paid to occurrences, especially the arts which were of no interest to either the colonial administration or the Anthropology researcher. It took combined efforts of the then Organization of African Unity (O.A.U.) and the United Nations Educational, Scientific and Cultural Organization (UNESCO) to deconstruct the misconceptions created through an eight-volume of a General History of Africa between 1964 and 1999. These attempts by African historians to correct the damage exclusion and distortion of facts about Africa and Africans is laudable, however, a gap still remains. The historiography of African theatre which has its foundation in Africa’s oral traditions is minimal. A continent of such diverse artistic performances needs a huge representation of both indigenous and external theatrical traditions in Theatre History. Using the desk review approach, ideological criticism and content analysis, this paper argues that the lack of expertise in decoding indigenous language and expressions and fear of misrepresentation are the sources of the minimal presence of African Theatre Historiography.